EVALUASI KRITIS GREEN MARKETING SEBAGAI BRAND IMAGE PADA STARBUCKS TUNJUNGAN PLAZA SURABAYA - Indrawati, Mei (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This research was conducted at Starbucks Coffee Shop Tunjungan Plaza Kota Surabaya. The urgency of this study is understanding Starbucks' operations to the local environment, natural resource use, waste management, and contribution to environmental problems. The formulation of the research problem is: 1) How is the implementation of green marketing at Starbucks Tunjungan Plaza Kota Surabaya? 2) How can green marketing become a brand image in the community? 3) What are the obstacles faced by Starbucks in implementing green marketing strategies and practices in the city of Surabaya? This research method is a qualitative descriptive study that explains phenomena based on research findings combined with the use of relevant theories. This research data analysis technique includes data triangulation based on primary data and secondary data. The results showed Starbucks coffee shops created a significant positive impact through recycling programs, coffee bean sourcing and waste reduction. This combination has a high responsibility and concern for the environment that gives rise to a strong emotional attachment with customers. The secret to the success of Starbucks coffee shops is the combination of green marketing and a strong brand image that is the main driver of sustainable business success in society and the environment.